2020
DOI: 10.1029/2019jc015430
|View full text |Cite
|
Sign up to set email alerts
|

Source Regions of Infragravity Waves Recorded at the Bottom of the Equatorial Atlantic Ocean, Using OBS of the PI‐LAB Experiment

Abstract: Infragravity waves are generated along coasts, and some small fraction of their energy escapes to the open oceans and propagates with little attenuation. Due to the scarcity of deep-ocean observations of these waves, the mechanism and the extent of the infragravity waves energy leakage from the coasts remains poorly understood. Understanding the generation and pathways of infragravity wave energy is important among others for understanding the breakup of ice-shelves and the contamination of high-resolution sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Although the model failed to explain significant FIG energy levels that occurred prior to the peak of storms at the measurement site in the central North Sea (suggesting that other processes also contributed to FIG energy at this location), the overall model‐data agreement suggests that a significant fraction of the FIG energy levels in the southern North Sea originated from distant shorelines. These results are in accordance with previous studies on the shelf or near the shelf break (e.g., Harmon et al., 2012; Smit et al., 2018; Tonegawa et al., 2018) and in the deep ocean (e.g., Bogiatzis et al., 2020; Crawford et al., 2015; Neale et al., 2015; Rawat et al., 2014) that linked significant energy at IG frequencies to radiation of FIG from distant shorelines.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the model failed to explain significant FIG energy levels that occurred prior to the peak of storms at the measurement site in the central North Sea (suggesting that other processes also contributed to FIG energy at this location), the overall model‐data agreement suggests that a significant fraction of the FIG energy levels in the southern North Sea originated from distant shorelines. These results are in accordance with previous studies on the shelf or near the shelf break (e.g., Harmon et al., 2012; Smit et al., 2018; Tonegawa et al., 2018) and in the deep ocean (e.g., Bogiatzis et al., 2020; Crawford et al., 2015; Neale et al., 2015; Rawat et al., 2014) that linked significant energy at IG frequencies to radiation of FIG from distant shorelines.…”
Section: Discussionsupporting
confidence: 93%
“…Other deep water infragravity generation mechanics have also been proposed, such as atmospheric forcing by wind speed fluctuations (de Jong & Battjes, 2004;Vrećica et al, 2019) and IG-tidal interactions (Sugioka et al, 2010). By linking the arrival of FIG waves at oceanic sites to the landfall of energetic sea-swell waves at distant coastal regions, most deep water observations of IG energy have been explained by radiation of FIG waves at distant shorelines (e.g., Bogiatzis et al, 2020;Godin et al, 2014;Harmon et al, 2012;Neale et al, 2015;Tonegawa et al, 2018). Coastal regions with a narrow shelf that are subject to energetic sea-swell waves are generally believed to be a major radiator of FIG waves, although details regarding the dependence of FIG radiation on environmental conditions such as the sea state (e.g., the directional spreading and incident angles of sea-swell waves) and the coastal morphology is less well understood (Crawford et al, 2015;Smit et al, 2018).…”
mentioning
confidence: 99%
“…Here, we present results from the Passive Imaging of the Lithosphere Asthenosphere Boundary (PI-LAB) experiment and the Experiment to Unearth the Rheological Oceanic Lithosphere-Asthenosphere Boundary (EURO-LAB) at the equatorial Mid Atlantic (Harmon et al, 2018Agius et al, 2018Agius et al, , 2021Bogiatzis et al, 2020;Hicks et al, 2020;Leptokaropoulos et al, 2021;Rychert et al, 2021;Saikia et al, 2020Saikia et al, , 2021Wang et al, 2020), which was designed to image the base of the tectonic plate and determine what makes a plate, plate-like (Rychert et al, 2005(Rychert et al, , 2016(Rychert et al, , 2018a(Rychert et al, , 2018bRychert & Shearer, 2009). In this study, we image the upper mantle Q μ −1 beneath the equatorial Mid-Atlantic Ridge.…”
Section: 1029/2021gc010085mentioning
confidence: 99%
“…These studies found that the lithosphere-asthenosphere boundary beneath the Atlantic is defined to first order by temperature, but that it is also dynamic and dictated by variations in melt generation and migration (Fischer et al, 2020;Harmon et al, 2018Harmon et al, , 2021Rychert et al, , 2021Wang et al, 2019Wang et al, , 2020Saikia et al, 2021a,b). A number of other studies were possible with the data including, for instance, locating the source regions of infragravity waves (Bogiatzis et al, 2020), local seismicity work (Hicks et al, 2020;Leptokaropoulos et al, 2021Leptokaropoulos et al, , 2022Schlaphorst et al, 2022), sediment constraints (Agius et al, 2018;Saikia et al, 2020), mantle transition zone imaging (Agius et al, 2021), and the work presented in this manuscript. In the experiment 24 OBSs were equipped with a Nanometrics T-240 broadband seismometers (Fig.…”
Section: Introductionmentioning
confidence: 99%